Performance of Argon-Xenon Mixtures in a Gas Proportional Scintillation Counter for the 0.1–10 keV X-Ray Region - Carmo, S. J. C. do (2009)
The performance of a gas proportional scintillation counter filled with either pure Xe or Ar-Xe mixtures is described for the 0.1-10 keV X-ray energy range. It is shown that the spectra tail distortion exhibited by Xe filled gaseous detectors for soft X-rays below 2 keV is reduced if Ar-Xe mixtures are used. The peak-to-valley ratio increases by a factor of about 2 or 3 as the Xe concentration is reduced from 100% to 5%. Moreover, the energy resolutions for such mixtures are similar to the ones for pure Xe